Membangun Citra Pendidikan Kejuruan: Manfaat dan Implikasinya Bagi Perbaikan Kualitas Output dan Outcome - Dardiri, Ahmad (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2012)
One of the serious problems faced by Vocational School (SMK) is currently low image perception in the community. Low interest in enrollment, low public supports in class implementation, low industry participation in vocational learning are several indicators of the poor image. This is certainly an obstacle to the successful development of vocational education efforts. Meanwhile, vocational education is an education that focuses on preparing Indonesian youth to enter their world of work. Thus, the condition becomes a challenge to principals‟ leadership in establishing image/promoting. Vocational education development has strong justified philosophical, social, economic and employment aspects. The process of building image requires proper marketing strategies including positioning, differentiation, and school excellence branding. Good image is believed to improve quality of inputs, increase industrial public confidence, increase communities‟ participation and pride to support vocational education, which in turn can improve quality of outputs and outcomes of the vocational education.